PROPOSITION FOR (DIS)ABLED BODIES INCLUSION AT PHYSICAL EDUCATION CLASSES (Fiep Bulletin - online, 2014)
Qualitative research aiming to include (dis)abled students in physical education classes. We propose adaptations in swimming, soccer, gymnastics, badminton and volleyball, identifying different senses in activities that compose people's imaginary with special conditions to these practices - paralyzed bodies and/or mutilated, sensory and/or mental limitations. As a methodological procedure, we accomplished Selection and Analyses of Adapted Physical Education Content and Routine Observations with (dis)abled bodies, during the activities of the supervised internship in physical education, in public and private pre-schools and middle schools, in Rio de Janeiro state. Our challenge was to explain, through the adapted physical activities enchantment, the complicity of teachers and other students, how the (dis)abled metamorphose their apparent disability, covering it with expressions, encoded signals and established in different languages. We thought again about these practices by (re)reading aesthetic, symbolic, defying, and social aspects, giving them efficient color. This physical education is justifiable by subsidizing a body movement practice expressed in games, dances, fights, sports and gymnastics. This study is found in the introductory phase. During the Supervised Internship period, we observed that including controversial themes in physical education classes will stimulate a reflection and will allow the development of citizens who will participate in physical activities without sex, age, or race prejudice (PCN's, 2000). This way, these bodies, discovery agents, achieve the well dreamed of inclusion. Spirit flows through the body, (re)writing each (dis)abled movement, printing them with new colors, achieving imaginary dimensions and humanizing Nature, where impossibility was replaced by the space occupied by the disable body, movement flowed, languages updated body senses. When giving a new meaning to physical activities they surpass rules and strict techniques, allowing wheels, motion, adventurous spirit, other-body and world-body and thing-body senses to win life, posture, body attitude and to propagate from one body to another.
Keywords: physical education; inclusion; (dis)abled bodies